Induction of H7N9-Cross-Reactive Antibody-Dependent Cellular Cytotoxicity Antibodies by Human Seasonal Influenza A Viruses that are Directed Toward the Nucleoprotein. (23rd December 2016) - Jegaskanda, Sinthujan; Co, Mary Dawn T.; Cruz, John; Subbarao, Kanta; Ennis, Francis A.; Terajima, Masanori
Abstract: Antibodies that mediate antibody-dependent cellular cytotoxicity (ADCC) against avian influenza virus subtypes, including H7N9 and H5N1, have been detected in human sera. Using NK cell activation and NK cytotoxicity assays, we compared ADCC-mediating antibodies (ADCC-Abs) in sera collected from healthy infants, children and adults against H7N9 virus–infected cells and recombinant hemagglutinin (HA), neuraminidase (NA), and nucleoprotein (NP) proteins. High titers of ADCC-Abs against H7N9 virus–infected cells were detected in sera from adults and children but not infants. ADCC-Abs titers directed against H7N9 HA or NA proteins. Further analysis showed that ADCC-Abs titers were significantly higher toward H7N9 NP, as compared with H7N9 HA or NA proteins, and correlated strongly with ADCC-Abs titers against H7N9 virus–infected cells. Indeed, ADCC-Abs to NPs of seasonal H1N1 and H3N2 viruses correlated strongly with ADCC-Abs to H7N9 NP, suggesting that seasonal influenza infections and vaccinations may induce these cross-reactive antibodies. Targeting ADCC-Abs to internal proteins may be a potential mechanism of universal vaccine design.